Implementing land evaluation and site assessment (LESA system) in farmland protection: A case‐study in northeastern China. (9th March 2021) - Qian, Fengkui; Wang, Weiwen; Wang, Qiubing; Lal, Rattan
Abstract: Farmland evaluation has become a major topic in farmland protection research. Due to the lack of reasonable and scientifically reliable evaluation methods for farmland protection, the farmland of quality and covering a wide area are at high risk of degradation and destruction in China due mainly to rapid industrialization and urbanization. The land evaluation and site assessment (LESA) system has been successfully applied to protect important farmland globally. To better understand and testify the flexibility and suitability of the LESA system for farmland protection in different geomorphic regions in China, we investigated the delineation of basic farmland by applying and testing the LESA system in Liaoning Province of China. In this study, the LESA system was constructed and comprehensively evaluated through the land evaluation (LE) and site assessment (SA) subsystems; soil conditions suitable for agriculture and site conditions feasible for other land uses were selected in the LE and SA subsystems, respectively. The results demonstrated that the ratios of the LE and SA subsystems were 6:4, 5:5, and 4:6 in the middle plain area (MPA), eastern mountainous area (EMA), and western hilly area (WHA), respectively. Farmlands with LE scores over 80 accounted for 80.7%, 34.7%, and 28.6% in the MPA, WHA, and EMA, respectively. Moreover, 37.2% of farmland with high SA scores (over 50) was primarily distributed in the WHA, and only 7.1% and 0.4% in the MPA and EMA, respectively. The farmland ratios with LESA scores over 60 were 74.8%, 52.2%, and 30.2% in the MPA, EMA, and WHA, respectively. In particular, the total farmland was grouped into three primary categories, which scientifically demonstrated the suitability and compatibility of the farmland features and also provided guidance for the implementation of farmland consolidation and remediation techniques.